Parenting practices that help promote the development of positive social behavior among preschool children within the family - De Leon, Maria Perlita Embuscado (2010.)
ABSTRACT This research used data from fifteen 2-paent families residing in a community in Dalandan, Valenzuela City, with at least two children and one of whom is between the ages 3 to 6 years old. Seven of these families are dual-earner and the remaining eight are single-earner with only the husbands as breadwinners. The research locale is urbanizing area that is transitioning from agricultural to industrial source of livelihood. The particular focus of this research include (1) to identify the behaviors which parents define as pro-social, (2) to explore parents' perception about their roles, influences, and parenting practices in teaching pro-social behavior to their preschool children, (3) to discuss socialization patterns within the family that help promote the development of positive social behavior among preschool children, and (4) to determine the ideas, opinions, and feelings of the preschool children in the manner by which they are being disciplined and taught positive social behaviors. The research utilized a classical mini-ethnographic approach which allowed for a 6-month field study through home visits and informal conversations with the participating families. Storytelling sessions were conducted among the 18 preschoolers from the 15 participating families after the 6-month home visits. finally, face to face interview were also conducted with the parents of those families. The findings of the research suggest that local concept that is best related to pro social behavior is "mabuting asal" which is also an umbrella term that covers not only pro social attitudes but also positive social behaviors such as having love of God, having integrity, being responsible, and studying well. The parents also believed that children are naturally naive,passive and forgetful, thus their primary role in developing pro social behavior to their children is to teach them proper rules of behavior, to model to their young ones what proper behaviors are, and to remind them constantly of what to do and not what to do. It was also found out that parents in dual-earner families highlighted the importance of studiousness, whereas fathers from both single and dual-earner groups noted the importance of having social behaviors geared towards the development of oneself and care for the family, especially towards younger siblings. Three direct methods were reportedly used by the parents in teaching the children pro social behavior and these are physical, verbal and cognitive approaches. Both single and dual-earner families use this method especially when they feel the transgressions are grave. Mothers in dual-earner families observe the use of physical and cognitive methods more often than do mothers in the single-earner group. Mothers in both groups observe the use of cognitive method more than fathers do. Fathers in both groups observe the use of verbal method more than mothers do. Fathers in single-earner groups observe the use of cognitive method than their dual-earner counterparts. The findings further suggest that the micro system of the home, specifically the parents own influences to their children, is believed to be the environment which best promotes the development of positive social behavior among young children. There were also identified elements in the microsystem of the neighborhood which both facilitate and inhibit the development of proper social conduct. The influences which parents identified as contributory to their ideas and practices about teaching positive social behavior to young children include individual experiences, familial experiences, and social groups and institutions surrounding them. The experiences of harsh and coercing parenting style from their own mothers and fathers of the fathers' in both single- and dual-earner families, created in these parents either modeling or compensating parenting behavior towards their own children. Meanwhile,social network, work environment and media, social and church were among the social groups and institution which affected the parents most in their childrearing practices. For both single and dual-earner mothers and fathers of these parents, the school, through the teacher, and the media serve as source of information for proper childcare and nurturance. Parents in dual-earner families find their social network as support system in providing childcare and as agent in mediating parental stress brought by employment. Fathers in both income groups and mother in dual-earner families recognized employment not only as a source4 of bread and butter but also a factor that indirectly affects the parent-child relationship. There were also certain socialization patterns within the family system that may either promote or hamper the development of pro social behaviors among pre-school children upon analysis of the observed behaviors between the parent-child dyads based on molar activities, interpersonal structures, roles, communication patterns, and parental patterns of behavior. Molar activities common to both single and dual-earner families and these are eating together, sharing stories together, watching television and studying together, playing with each other and going out to visit friends or relatives or go to the mall while attending church service was found to be unique only to dual-earner families. Single earner parents were also observed to be more involved during the conduct of those activities. Father in the dual-earner groups, on the other hand, were engaged in low energy activities like watching TV or chatting with the children. There were different interpersonal structures within the microsystem of the family that promotes the social, emotional and cognitive development of the child and these are the mother-child, father-child, and siblings dyads as well as the parent-children microsystem. It appeared that cognitive development of the children was usually facilitated better between the mother-child and sibling dyads for both dual and single-earner families. Socio-emotional development was best promoted in the father-child dyads and the parent-children microsystem for both dual and single- earner families. Family members have different roles to play within the family system. These roles include earning a living, decision making, performing household chores, performing childcare, disciplining the children and the tasks of young children in the family. Roles were more explicitly assigned in single-earner and implicitly assumed in dual-earner families. Moreover, task differentiation among the children was primarily based on their age and birth order rather than their gender. Dual-erner parents have a longer lists of behavior they value. This was attributed of maternal work experiences and transmitted through their rules of proper social conduct and high involvement in nurturing their young ones. Single-earner families have characteristically more open communication between parents and children while dual-earner families show more close communication. The positive quality of communication within the marital relationship was likewise highlighted vas an influence to an open communication style among single-earner families. with respect to the patterns of parental behaviors observed, it was found out that both single- and dual-earner families have pattern of behavior that promote and do not promote prosocial behavior. Dual-earner parents displayed more behaviors that do not promote prosocial conduct through both their non hostile means of dealing with their children despite their attempts to display positive affect to the children.
Thesis (M.A. Psychology)--University of the Philippines Diliman
Keywords: Child rearing -- Philippines -- Valenzuela City; Parent and child -- Philippines -- Valenzuela City; Parenting -- Philippines -- Valenzuela City; Socialization -- Philippines -- Valenzuela City